Avaliação do potencial biomodificador do extrato de urucum em colágeno dentinário na terapia fotodinâmica antimicrobiana - Lourenço, Gabriela Araujo (2023)
The degradation of the hybrid layer is caused by damages of exogenous and endogenous origin, inherent to the technique or biological causes, constituting an important factor for failures in adhesive procedures in restorative dentistry. The biomodification of dentin collagen composes one of the important steps for the integrity of these restorations. The aim of this study is to evaluate the biomodification potential of annatto extract as a photosensitizer for Antimicrobial Photodynamic Therapy (APDT) in dentin collagen. For this purpose, dentin bars (0.5x1.7x6.0mm) were fabricated, which were demineralized for 5 hours in 10% phosphoric acid and distributed into the following groups: distilled water (negative control); 6.5% grape seed extract (GSE); 10% annatto extract (URU); 10% annatto extract associated with APDT for 40 seconds (URU + 40s), and 10% annatto extract associated with APDT for 3 minutes (URU + 3min). Quantitative tests of elastic modulus (EM) [n=10], mass variation (ΔM) [n=10], and color change (ΔE) [n=10] were performed using a universal testing machine, precision balance, and digital spectrophotometer, respectively, at different time points (before and after biomodification, 7, 14, and 30 days of storage), and biodegradation test [n=10], in addition to Fourier Transform Infrared Spectroscopy (FT-IR) for qualitative analysis of the formed bonds. Data were subjected to Kolmogorov-Smirnov normality test, resulting in values outside the normal distribution for EM, ΔM, and ΔE tests. Friedman test was applied for intergroup analysis and Kruskal-Wallis for intragroup analysis, both with Tukey's post hoc test (p<0.05). Biodegradation test obtained data within normality, thus one-way ANOVA with Tukey's post hoc test (p<0.05) was used. It was observed that the AE group was effective in elevating EM in the studied time points, URU + 40s and URU + 3min were effective at 7 and 14 days, respectively. When analyzing ΔM, there was no statistically significant difference when comparing the test groups to the control group. In intragroup analysis, URU + 3min showed mass reduction after 7 days, and URU + 40s presented decreased weight after 14 days after biomodification. URU + 40s and URU + 30m groups were able to maintain the structure of collagen under the challenge of bacterial collagenase biodegradation. FT-IR spectra demonstrated that all solutions interacted with collagen to some extent. There was color change in the test groups compared to the negative control, however, there was no statistical difference when compared to each other. It is concluded that annatto extract was effective in promoting dentin biomodification by elevating EM and maintaining collagen mass in the observed time points. When associated with APDT, it was able to resist the challenge of bacterial collagenase biodegradation. Residual staining on the substrate may be a limitation for use in esthetic areas.